The land of the dead - Osborne, Mary Pope (Mary Pope Osborne's Tales from the Odyssey, 2002)
A retelling of part of the Odyssey in which Odysseus and his fleet continue their journey and encounter giant cannibals, a beautiful witch, and the Land of the Dead.